Cannabinoids for Pain Control During Medical Abortion: A Randomized Controlled Trial. Issue 6 (June 2020) - Colwill, Alyssa Covelli; Alton, Katie; Bednarek, Paula H.; Bayer, Lisa L.; Jensen, Jeffrey T.; Garg, Bharti; Beardsworth, Kathleen; Edelman, Alison
Abstract : OBJECTIVE: To evaluate whether prophylactic dronabinol, a synthetic tetrahydrocannabinol, reduces pain during medical abortion. METHODS: We conducted a randomized, double-blind, placebo-controlled trial of women undergoing medical abortion with mifepristone and misoprostol up through 70 days of gestation. All participants received 800 mg of ibuprofen and were randomized to either 5 mg of oral dronabinol or a placebo 30 minutes before misoprostol administration. Participants used a text messaging service to report pain on a numeric rating scale from 0 to 10 (0=no pain, 10=worst pain). The primary outcome was maximum pain experienced during the 24 hours after misoprostol administration. Secondary outcomes were pain scores at 0, 6, and 24 hours after misoprostol administration; maximum anxiety and nausea scores; use of additional pain medication; reported side effects; and satisfaction (yes or no). We needed 68 participants (34 per group) to have 80% power to detect a 2-point difference in maximum pain on a numeric rating scale. RESULTS: From November 2018 to May 2019, we randomized 70 women (dronabinol=35, placebo=35). Participants in the study arms had comparable baseline characteristics. We found no difference between groups in the median maximum pain score reported (dronabinol 7 [interquartile range 6–8], placebo 7 [interquartile range 5–8], P =.82) or median pain scores at any timepoint. Groups were also no different in mean maximum anxiety (dronabinol 3.33 [SD 3.06], placebo 3.23 [SD 2.53], P =.88) or nausea scores (dronabinol 2.21 [SD 2.32], placebo 2.72 [SD 2.64], P =.41). Most women were satisfied with their pain management (76% dronabinol, 82% placebo, P =.51). CONCLUSION: Dronabinol does not reduce the maximum level of pain experienced by women undergoing medical abortion. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT03604341. Abstract : Prophylactic dronabinol, a synthetic form of tetrahydrocannabinol, does not reduce the amount of pain experienced by women undergoing medical abortion or improve anxiety, nausea, or satisfaction.